Assessment of climate change impacts on energy generation from renewable sources in Croatia - PASICKO, Robert; BRANKOVIC, Cedo; SIMIC, Zdenko (Renewable energy, 2012)
Although the subject of climate change attracts enormous attention, there is limited number of analyses dealing with climate change impacts on the power system planning. It is important to understand these influences since the power system planning must consider very long time spans, and therefore it might be affected by potential climate change in multiple ways. This study focuses on the initial evaluation of climate change impacts on renewable energy sources in Croatia - specifically, photovoltaic, wind and hydro energy. The climate data used for this assessment were taken from the global climate model ECHAM5-MPIOM and dynamically downscaled by the regional climate model RegCM at Croatian Meteorological and Hydrological Service (DHMZ). The results based on the IPCC A2 scenario for the two future climate time periods, 2011–2040 and 2041–2070, are analyzed. The climate change that would potentially have the most significant impact on renewables is expected in the coastal and adjoining areas of Croatia during summer where an increase by 20% in the mean wind speed is projected already for the first time period, and more than 50% until 2070. This would, theoretically, imply almost a doubling in electricity production even in the first period. The impact of climate change on electricity production from photovoltaics might be neutral since it is balanced by opposing dominant factors, while a reduction of more than 10% in the production of electricity from hydro power plants could be expected after 2050. Estimates of uncertainties related to climate change are necessary in order to be able to determine the importance of climate change impacts on the future power generation from renewable energy sources. ► We modelled future climate change impact on Croatian renewable energy sources. ► Climate change impacts on nine different climate variables were checked, and their impact on renewables was analyzed. ► Wind energy generation might increase significantly due to climate change impacts already until 2040. ► Hydro energy generation might decrease significantly due to climate change impacts. ► Impact of climate change on photovoltaics might be neutral.